DNA measurements after radiation-induced tissue structure of thyroid gland of rats Análise do conteúdo de DNA (ploidia) em tecidos de glândula tireóide de ratos após indução por radiação - Roberto Souza Camargo; Neuza Kasumi Shirata; Eliana Ogassavara Setani; Eduardo Anselmo Garcia; Eduardo Pompeu; Eduardo Martella; Celso di Loreto; Adhemar Longatto Filho (Sociedade Brasileira de Patologia Clínica, 2005)
INTRODUCTION: Thyroid gland exposures to radiation induce nuclear chromosomal alteration. Objective: To evaluate the DNA content of thyroid gland submitted to radiation. MATERIALS AND METHODS: We radiated 75 rats while 25 were not radiated to be used as control group. Exposure was conducted by the use of Cobalt-60 radioactive source in the right anterior cervical region in a field of 3-30cm, comprising the second and the sixth tracheal rings with 600-centigray (cGY) doses. The DNA content (ploidy) was obtained with Feulgen-thionin stain and was quantified with CAS 200 quantitative measurement equipment. RESULTS: Diploid pattern was obtained in 88 cases (95.7%), independently of time of exposure: on the other hand, aneuploidy was observed in four cases (4.3%) only in the group sacrificed to the 33 days. Eight cases were excluded due to technical reasons. CONCLUSION: The early aneuploid pattern found in our study certainly corroborated that radiation affects thyroid gland with important consequences in terms of disorders. INTRODUÇÃO: A exposição da tireóide à irradiação está associada à alteração do componente cromossômico nessa glândula. OBJETIVO: Avaliar o conteúdo de DNA (ploidia) em glândula tireóide submetida à radiação. MATERIAL E MÉTODOS: Foram irradiadas tireóides de 75 ratos; 25 foram usados como grupo controle e não sofreram irradiação. A exposição à irradiação foi realizada com o uso de Cobalt-60 na região cervical anterior direita com espaço de 3-30cm, com anel traqueal de 2º e 6º e dose de 600 centigrays (cGY). O conteúdo de DNA (ploidia) foi obtido com o método de Feulgen-Thionin e quantificado com o aparelho CAS 200 de citometria estática. RESULTADO: Dos 92 casos, 88 (95,7%) foram diplóides, independente do tempo de exposição; aneuploidia foi observada em quatro casos (4,3%), somente no grupo sacrificado aos 33 dias. Oito casos foram excluídos por problemas técnicos. CONCLUSÃO: A irradiação afeta muito precocemente o conteúdo de DNA nuclear levando a aneuploidia.